PELATIHAN SISTEM AKUNTANSI DAN PENYUSUNAN LAPORAN KEUANGAN UNTUK USAHA PEMBUATAN PAKAIAN PADA CMT - Ekadjaja, Agustin; Wahid, Norman (Jurnal Serina Abdimas, 2024)
In conducting business activities and trading, accounting is a very important and strong provision in the course of business operations. Learning accounting does take a long time to form a strong foundation. However, it is never too late, especially for UMKM actors in the community who start businesses self-taught and carry out business activities independently. The existence of UMKM in the community is a very positive thing in building the Indonesian economy. Although the scale of the business carried out is not yet large, the application of UMKM by the community carried out in large numbers and in varied industries raises good economic potential for economic progress. Therefore, the PKM team sees that Accounting theory training can be one way to take a role in the economic development of UMKM. With adequate accounting provision, UMKM actors can use theories that have been tested and in accordance with standards to manage their business economy and make their business better. The training conducted by the PKM team targeted one of the UMKM engaged in garment and clothing design located in West Jakarta.